Pengembangan Media Pembelajaran Akidah Akhlak Berbasis Google Sites Dalam Menumbuhkan Kemampuan Berpikir Kritis - Syarip Hidayatullah; Maswani Maswani; Abdul Ghofur (Universitas Negeri Padang, 2023)
The challenges of the 21st century and the start of the 4.0 era change the face of education to be more competitive, demanding educators to be more innovative and creative in designing learning. In facing these conditions, it is necessary to equip students with critical thinking skills emphasizing the use of technology in learning. The purpose of this research is to develop learning media for moral akidah based on Google Sites in fostering critical thinking skills of seventh-grade MTs students on the material of riya’ and nifaq. This type of research is the Research and Development model Borg and Gall with data collection techniques of interviews, observations, documentation, questionnaires, and tests. The data analysis technique for qualitative data is the Milles and Huberman model, while the independent samples t-test and N-Gain calculation are used on quantitative data. The development results are very good and representative of fostering students’ critical thinking skills. This is evidenced by the assessment of material experts with a percentage of 91.2%, the assessment of media experts shows a percentage of 98.4%, and the assessment of moral creed subject teachers with a percentage of 100%. The effectiveness of google sites learning media can be observed from the results of the independent samples t-test test with a significance value of 0.000 <0.05 with a comparison of the t_hit value of 4.869> 1.671 t_tab which means H_0 is rejected, and H_1 is accepted. The increase in students’ critical thinking skills can be seen in the calculation of N-Gain = 0.4178 with a “moderate” improvement category.